Good practice in occupational health services: Prophylactic care and occupational activation of people with disabilities due to respiratory diseases - Marta Wiszniewska; Diana Tymoszuk; Agnieszka Lipińska-Ojrzanowska; Ewa Wągrowska-Koski; Jolanta Walusiak-Skorupa (Nofer Institute of Occupational Medicine, 2013)
Respiratory diseases are a cause of long-term sickness absence, and even of partial or complete inability to work. This paper presents the first in Poland description of principles of good practice in occupational health service provided for people with respiratory diseases. The issues concerning the certification of the ability to work in this group of patients are discussed. The key-principles of preventive care of workers with obstructive and interstitial lung diseases with particular attention paid to the control of major risk factors are also presented. The importance of possible contraindications for job performance by workers affected by these diseases, as well as the responsibilities of occupational health physicians were highlighted. Med Pr 2013;64(3):427-438